Identification and characterization of a novel bipartite nuclear localization signal in the hepatitis B virus polymerase - Lupberger, Joachim (Baishideng Publishing Group Co., Limited, 2013)
AIM: To characterize the nuclear import of hepatitis B virus (HBV) polymerase (P) and its relevance for the viral life cycle. METHODS: Sequence analysis was performed to predict functional motives within P. Phosphorylation of P was analyzed by in vitro phosphorylation. Phosphorylation site and nuclear localization signal (NLS) were destroyed by site directed mutagenesis. Functionality of the identified NLS was analyzed by confocal fluorescence microscopy and characterizing the karyopherin binding. Relevance of the structural motives for viral life cycle was studied by infection of primary Tupaia hepatocytes with HBV. RESULTS: We identified by sequence alignment and functional experiments a conserved bipartite NLS containing a casein kinase II (CKII) phosphorylation site located within the terminal protein domain (TP) of the HBV polymerase. Inhibition of CKII impairs the functionality of this NLS and thereby prevents the nuclear import of the polymerase. Binding of the import factor karyopherin-α2 to the polymerase depends on its CKII-mediated phosphorylation of the bipartite NLS. In HBV-infected primary Tupaia hepatocytes CKII inhibition in the early phase (post entry phase) of the infection process prevents the establishment of the infection. CONCLUSION: Based on these data it is suggested that during HBV infection the final import of the genome complex into the nucleus is mediated by a novel bipartite NLS localized in the TP domain of HBV polymerase.